2000
DOI: 10.1097/00007632-200003010-00016
|View full text |Cite
|
Sign up to set email alerts
|

Foraminal Epidural Extra Osseous Cavernous Hemangioma of the Cervical Spine

Abstract: Clinical and radiologic presentation could be confusing in a purely foraminal epidural cervical cavernous hemangioma. Cavernous hemangioma must be known as a differential diagnosis of a foraminal schwannoma. Diagnosis of cavernous angioma is made easily on pathologic examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 10 publications
2
28
0
6
Order By: Relevance
“…In our study, 2 cases demonstrated sudden onset myelopathy caused by an epidural hematoma in the background of a cavernous hemangioma. This finding was similar to that of Carlier et al 22 The differential diagnosis of spinal epidural hemangiomas included herniated disks, synovial cysts, granulomatous infections, neurogenic tumors, lymphomas, meningiomas, angiolipoma, pure epidural hematoma, and epidural extramedullary hematopoiesis depending on the MR types 5,8,11,[14][15][16][17][18][19] (On-line Table 2). In type A or B, spinal epidural hemangiomas were seen as a cystlike mass with peripheral enhancement.…”
Section: Fig 2 Case 2 a Cystlike Mass With T1 Isointensity (Type B)supporting
confidence: 86%
See 1 more Smart Citation
“…In our study, 2 cases demonstrated sudden onset myelopathy caused by an epidural hematoma in the background of a cavernous hemangioma. This finding was similar to that of Carlier et al 22 The differential diagnosis of spinal epidural hemangiomas included herniated disks, synovial cysts, granulomatous infections, neurogenic tumors, lymphomas, meningiomas, angiolipoma, pure epidural hematoma, and epidural extramedullary hematopoiesis depending on the MR types 5,8,11,[14][15][16][17][18][19] (On-line Table 2). In type A or B, spinal epidural hemangiomas were seen as a cystlike mass with peripheral enhancement.…”
Section: Fig 2 Case 2 a Cystlike Mass With T1 Isointensity (Type B)supporting
confidence: 86%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][20][21][22][23] According to our results and previous reports, the most common MR features of cavernous spinal epidural hemangiomas were solid hypervascular masses with lobular contour. There have been only 2 case reports describing MR features of other types of spinal epidural hemangiomas.…”
Section: Discussionsupporting
confidence: 54%
“…Обычно ПГ не имеют клинических проявлений и случай-но обнаруживаются при проведении КТ или МРТ позвоночника. Однако в редких случаях ПГ носят агрессив-ный характер, манифестируя симпто-мами резистентной к медикаментам боли и неврологическим дефици-том [2,3,6,7,10,14,19,21,22,28,30,35,37,39]. Это происходит в случа-ях диффузного поражения позвонка, патологического перелома его тела, а также из-за проникновения опухо-ли в позвоночный канал с компрес-сией нервных структур [7,21,28,37].…”
Section: результаты и их обсуждениеunclassified
“…Боль локализовалась в месте поражения позвонка и яви-лась причиной снижения физической активности. По мнению некоторых авторов, болевой синдром обусловлен феноменом ангиогенных тромбозов, ишемией в виде синдрома обкрады-вания, а также натяжением передней и задней продольных связок из-за рас-ширения позвонка кавернозным ком-понентом опухоли [6,11,20].…”
Section: результаты и их обсуждениеunclassified
See 1 more Smart Citation